THE INFLUENCE OF PRICES AND SALES ON THE FINANCIAL STRATEGY IN THE CONTEXT OF AN ECONOMIC CRISIS - Nussupekova A.; Yerzhanov M.; Yerzhanova A. (Academics and Science Reviews Materials, 2023)
One of the parts of the formation of a financial strategy in a crisis is the choice of alternatives to the financial strategy for overcoming the global economic crisis and forecasting financial activities. Currently, scientists and practitioners have developed approaches and models that make it possible to reasonably approach the definition of company’s strategy. This article examines the aspect of identifying alternatives to the financial and economic strategy and its components: such as commodity; pricing, capital management strategy, and so on, associated with changes in sales volumes and product prices